2022
DOI: 10.1002/bse.3258
|View full text |Cite
|
Sign up to set email alerts
|

Does firms' carbon disclosure increase consumers' recycling willingness and firms' recycling performance?

Abstract: Nowadays, firms are expected to actively respond and take actions to respond to global warming and carbon emissions reduction. As a part of a circular economy, recycling improves waste management and reduces carbon emissions for firms. In the development of firms' strategies, the problem of enhancing the recycling performance becomes a challenge. This paper explores how carbon disclosure influences firms' recycling performance from consumers' purposive inference of firms' recycling behaviors. First, based on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 112 publications
0
1
0
Order By: Relevance
“…Luo's study found that various groups of individuals hold distinct viewpoints regarding the price premium of low-carbon buildings. Specifically, higher-income groups are more price-sensitive, while well-educated consumers are more inclined to pay a premium for green buildings [30,35]. Studies about the influence of green building characteristics on housing purchase tendency in foreign countries have also been conducted.…”
Section: Research Hypothesis 221 Impact Of Low-carbon Buildings On Co...mentioning
confidence: 99%
“…Luo's study found that various groups of individuals hold distinct viewpoints regarding the price premium of low-carbon buildings. Specifically, higher-income groups are more price-sensitive, while well-educated consumers are more inclined to pay a premium for green buildings [30,35]. Studies about the influence of green building characteristics on housing purchase tendency in foreign countries have also been conducted.…”
Section: Research Hypothesis 221 Impact Of Low-carbon Buildings On Co...mentioning
confidence: 99%
“…In that direction, we must first consider effects that are characteristic of ESG. One main effect is that ESG helps attract consumers, an observation supported by several research studies [20][21][22][23][24] and industry surveys showing that consumers prefer companies acting responsibly on social and environmental issues [3,[25][26][27][28][29][30]. However, attracting consumers is not the only effect associated with ESG investment.…”
Section: Introductionmentioning
confidence: 99%